A contribution to the identification of the critical plane using the maximum variance method. (December 2022) - Ferreira, J.L.A.; Dias, J.N.; Cardoso, E.U.; Araújo, J.A.; da Silva, C.R.M.
Highlights: A reformulation of the critical plane search strategy is introduced. The strategy provides accurate life estimates. The resulting algorithm is at least 230 times faster than other algorithms. The method is easy to implement. Abstract: The goal of the present paper is to propose a new critical plane search strategy based on the Maximum Variance Method of the resolved shear stress, to build a computationally efficient algorithm. For this, it is considered that the maximum variance of the shear stress resolved can be obtained by calculating the eigenvalues and eigenvectors of the covariance matrix of the resolved shear stress amplitudes in two perpendicular directions of a material plane. The evaluation of this strategy for different random multiaxial loading conditions shows that it compares very well with experimental data published in the literature.